Development and analysis of an open-source platform to simulate electric vehicle charging needs - Perez, Manuel Joaquim Andrade Sousa (2022)
There is the need to improve the charging process of EVs. In order to do that, the field of smart-charging and smart-charging algorithms emerged. Nevertheless, the studies involved in this field are complex, expensive, and risky, leading to a need for prior simulations to analyze/predict the integration of EVs in the electrical networks. There have been some solutions to solve this problem. However, they consist of either academic, proprietary, or limited/rigid solutions. On that account, in this thesis, we have presented a solution that provides a handy and intuitive tool for the researchers to simulate these scenarios with a decoupled and flexible simulation system. Its decoupled architecture is accomplished by adopting open design approaches and the concept of containerized micro-services, easing up the process of maintaining/extending it and providing high scalability. This solution was evaluated in three assessments: migrating it to a remote production system, giving an external developer the task of enhancing a given data model, and integrating this system with an external one. This solution delivered good results in these three tasks. All in all, this solution was motivated by the good aspects of some solutions found in the related work (and improving some of them), it fulfilled its objectives, and it solved the stated problem. At the moment, this solution is already up and running on a production system while also being consumed externally.